Pengaruh Media Perbanyakan Cendawan Entomopatogen Cordyceps militaris Fries Lokal terhadap Larva Oryctes rhinoceros L. di Laboratorium - Hamzah, Hamzah; Salbiah, Desita; Sutikno, Agus (Jurnal Agro Teknologi Tropika, 2016)
Pest control with usage entomopathogenic fungi opportunity was developing as biological control agent for example: Cordyceps militaris Fries local. The experiment was conducted in Plant Pest Laboratory from August until September 2015. The objectives study was to find the better prapagation medium for control rhinoceros beetles larvae (grubs). The experiment used completely randomized design (CRD) with three treatment and nine replication. The treatment tasted were maize, rice sifting and red seeds. The result showed that all propagation medium can be used to as propagation medium entomopathogenic fungi local Cordyceps militaris Fries and effective to control Oryctes rhinoceros L. grubs in laboratorium.